The effect of the photomagnetic poles strategy on learning the skill of spiking in volleyball - Hiba Abd Alrahman Azez; Najlaa Abbas Al-Zuhairi (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Objective: preparing educational units for the magnet poles strategy in learning the spiking skill in volleyball, and identifying the effect of the magnet poles strategy in learning the spiking skill in volleyball for female students. Research methodology: The experimental design with two equal experimental and control groups with tight control was also adopted in the pre- and post-tests. The boundaries of this research community are represented by fourth-grade middle school students at Basra Girls' Middle School (2024-2025), whose total number is (90) students, distributed by nature into 4 sections. Sections (A-B) were determined by lottery, so that Section (A) represents the experimental group and Section (B) represents the control group. Unsatisfied students and those who are frequently absent from the two groups were excluded. (15) students were randomly selected from each section, also by lottery, so that the total research sample reached (30) students, representing (33.3%) of this community. (15) students were also selected from Section (C) for the exploratory sample, representing (16.6%) of their original community Result: it is clear that the students of both the experimental and control groups all learned the skill of crushing in the results of the post-tests than they were in the results of the pre-tests. Conclusions: The strategy of the two poles of the light magnet can be applied in learning the skill of hitting the ball in volleyball for fourth-grade middle school students.